The role of cytokines in infertile patients with leucospermia and idiopatic oligoasthenospermia - Onur, Rahmi; Bodakçi, Mehmet Nuri; Firdolaş, Fatih; Orhan, Irfan; Gödekmerdan, Ahmet; Ardiço?lu, Aslan (My University, 2005)
Introduction: Oxidative stress has previously been shown to be related to increase in the levels of proinflammatory cytokines in seminal plasma of infertile patients. All of the measured cytokines seem to be produced locally as well as by white blood cells (WBC) and that, due to the presence of higher numbers of WBC, it was suggested that accessory gland infection may exert a deleterious effect on sperm quality through the production of ROS and/or of particular cytokines. In this study, seminal plasma cytokine levels were investigated in infertile patients with or without leucospermia and in control cases that have a normal semen analysis. Our aim was to determine the possible role of infection and inflammation in male infertility. Materials and methods: Three groups of patients were examined in our study. First group consisted of 10 patients who had oligoasthenospermia (OAS) with leukocytospermia, whereas in the second group we evaluated 10 patients who had OAS without leucospermia (isolated oligoasthenospermia) and negative mixed antiglobulin test (MAR). Finally, ten volunteer men who had normal fertility evaluations and at least one child (control group) constituted the control group and were included into the study. After a 3 to 5 days of abstinence period, ejaculate was obtained from all patients and the samples were left at the room temperature for 30 minutes. The samples were then centrifuged at 4000 rpm period for 10 minutes. Seminal plasma interleukin-2 (IL-2), IL-4 and tumor necrosis factor-? (TNF-?) levels were measured using ELISA in supernatant seminal plasma samples. Results: Measurement of seminal plasma cytokine levels in study and control groups revealed that the level of IL-2 was significantly increased in infertile patients without leucospermia (isolated oligoasthenospermia) than the other two groups. Seminal plasma cytokine measurement in patients with OAS plus leucospermia revealed statistically significant increase in the level of TNF-? when compared to the control and isolated OAS groups. Interleukin-4 levels did not show statistically significant difference between OAS and OAS plus leucospermia groups (p>0.05). Conclusion: Our data revealed that infection and increased cytokine levels may have roles in male infertility. The measurement of several cytokines in semen may provide clinically useful information for the diagnosis of male accessory gland infection, as well as in the absence of WBC where it can provide information about certain mechanisms of male reproductive function and dysfunction. However, to determine the exact role of cytokines in male genital system and to develop different methods for alternative diagnosis and treatment, there is still need for further studies.
Lökospermili ve idiyopatik oligoasstenopermik infertil hastalarda sitokinlerin rolü
Keywords: Cytokine; Infertility; Leucospermia; Seminal plasma